Integration of Renewable Energy into the Indian Power Grid: Electrical Engineering Challenges, Performance Trends, and Future Prospects (Academicia Review-A Multidisciplinary Online Journal, 2026)
India is undergoing one of the fastest renewable energy transitions in the world, with large-scale deployment of solar and wind power driven by national climate and energy security goals. While renewable integration offers environmental and economic benefits, it also presents significant technical challenges for power grid operation. This paper reviews recent developments (2024–2025) in renewable energy integration within the Indian power system from an electrical engineering perspective. Key issues such as intermittency, frequency stability, power quality, and grid flexibility are examined. Using a structured literature review and comparative analysis, the paper evaluates technological solutions including energy storage systems, grid-forming inverters, and smart grid technologies. A results table summarizes recent performance findings. The study concludes with future research directions to support a stable, resilient, and renewable-dominated Indian power grid
Keywords: Renewable energy; Indian power grid; electrical engineering